Incidencia de los factores relacionados con la eficiencia del Sistema Tributario Peruano sobre la informalización de las empresas entre los años 2009 al 2013. - Cavero Ramírez, Julianna Azucena (2014)
Informality is a separate phenomenon to the Peruvian economy, while the conditions of the economic structure of the country remain, their presence and importance are inevitable. Small taxpayers and/or informal, constitute a large number of individuals or economic units that provide a very small part of the collection due to their poor level of organization and the difficulty of imposing rigorous formal obligations. An analysis of the informal sector and its relationship with the tax system, based on the study of special tax regimes not provide us with consistent data regarding the impact of one variable on another in the case of taxes on informality, so which will be necessary to fully review the performance of our tax system and the mechanisms that may distort. This research aims to increase knowledge of the tax system in Peru and its relationship with informality, implying a greater understanding of the economic and redistributive impact of the national tax system and its structure, measured in terms of efficiency and causality informal, generate useful guidelines for developing tax policy that allows reducing the rate of informality in the economy with consequent advantages of this knowledge: improve revenue for the state and greater social inclusion for the informal worker.